Enhancing Taxpayer Compliance through Mobile SAMSAT Services: The Moderating Role of Tax Bleaching and Socialization - Khotmi, Herawati; Yani, Achmad; Astini, Yuli; Feryansyah, Feryansyah (Electronic Journal of Education, Social Economics and Technology, 2024)
Taxes represent the primary source of revenue for the state, whereas local taxes are derived from regional income. Consequently, enhancing awareness is essential to improve taxpayer compliance with their tax responsibilities. This research investigates the influence of mobile SAMSAT services, tax bleaching, and tax socialization on the compliance of motor vehicle taxpayers. Furthermore, it explores the role of mobile SAMSAT, tax bleaching, and socialization as moderating factors affecting taxpayer compliance. The analysis employs Structural Equation Modeling (SEM) utilizing the SmartPLS 4 software. The study's population consists of motorized vehicles registered in Mataram, with a probability sampling method applied to select a sample size of 100. Statistical analysis conducted with Smart PLS 4 indicates that tax bleaching positively influences taxpayer compliance, whereas mobile SAMSAT services and socialization do not have a significant effect. Additionally, the moderation analysis reveals that tax socialization enhances the relationship between tax bleaching and taxpayer compliance, but does not moderate the effect of mobile SAMSAT on compliance. The study recommends that future research incorporate additional variables, such as taxpayer awareness and taxpayer satisfaction.